First example of a heterobimetallic ‘Pd–Sn’ catalyst for direct activation of alcohol: efficient allylation, benzylation and propargylation of arenes, heteroarenes, active methylenes and allyl-Si nucleophiles - Das, Debjit; Pratihar, Sanjay; Roy, Ujjal Kanti; Mal, Dipakranjan; Roy, Sujit (Organic & biomolecular chemistry, 2012)
Arenes, heteroarenes, 1,3-dicarbonyls and organosilicon nucleophiles undergo highly efficient alkylation with allylic, propargylic and benzylic alcohols in the presence of a new 'Pd-Sn' bimetallic catalyst in nitromethane; water being the sole byproduct. The plausible mechanism of alkylation and the intermediacy of ether has been enumerated.